PENGARUH RETURN ON ASSETS, LEVERAGE, CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN KOMPENSASI RUGI FISKAL PADA TAX AVOIDANCE - Kurniasih, Tommy; Ratna Sari, Maria M. (Buletin Studi Ekonomi, 2013)
This research studied the impact of financial statement indicator to tax avoidance. ROA, leverage, corporate governance, company’s size, and fiscal lost compensation were used as an independent variable which were  assumed have an impact to tax avoidance (dependent variable) proxied by Cash Effective Tax Rates (CETR). This research used purposive sampling criteria and double linear regression analysis test. The result was ROA, leverage; corporate governance, company’s size, and fiscal lost compensation had a simultanous significant impact to tax avoidance in manufactur companies listed in BEI 2007- 2010 period. ROA, company’s size, and fiscal lost compensation influence tax avoidance partially and significantly. Leverage and Corporate Governance had no partial significant influence to tax avoidance. This result was consistent to previous research of Sari and Martani (2010)
Keywords: ROA, leverage, corporate governance, company’s size, fiscal lost compensation, tax avoidance